Update on state‐of‐the‐art for arterial spin labeling (ASL) human perfusion imaging outside of the brain. Issue 5 (6th February 2023) - Taso, Manuel; Aramendía‐Vidaurreta, Veronica; Englund, Erin K.; Francis, Susan; Franklin, Suzanne; Madhuranthakam, Ananth J.; Martirosian, Petros; Nayak, Krishna S.; Qin, Qin; Shao, Xingfeng; Thomas, David L.; Zun, Zungho; et al.
Abstract: This review article provides an overview of developments for arterial spin labeling (ASL) perfusion imaging in the body (i.e., outside of the brain). It is part of a series of review/recommendation papers from the International Society for Magnetic Resonance in Medicine (ISMRM) Perfusion Study Group. In this review, we focus on specific challenges and developments tailored for ASL in a variety of body locations. After presenting common challenges, organ‐specific reviews of challenges and developments are presented, including kidneys, lungs, heart (myocardium), placenta, eye (retina), liver, pancreas, and muscle, which are regions that have seen the most developments outside of the brain. Summaries and recommendations of acquisition parameters (when appropriate) are provided for each organ. We then explore the possibilities for wider adoption of body ASL based on large standardization efforts, as well as the potential opportunities based on recent advances in high/low‐field systems and machine‐learning. This review seeks to provide an overview of the current state‐of‐the‐art of ASL for applications in the body, highlighting ongoing challenges and solutions that aim to enable more widespread use of the technique in clinical practice.